The Nature of Predestination and the Character of the Predestinating God: A Reply to Christopher C. Emerick - Green, Chris E. W. (Journal of pentecostal theology, 2020)
This article is a reply to Christopher C. Emerick's reply to two articles the author has written on the doctrine of predestination, one of which offers a constructive proposal for the doctrine; the other sets out a creative reading of Romans 9-11. In this article, the author responds to Emerick's complaints, and points out the convergences and divergences in his understanding of the doctrine and the author's. Finally, the author will reiterate what he said previously, not only rephrasing what he said but also going beyond it in explanation for the sake of clarity.